2022
DOI: 10.1039/d2sc02080g
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric β-sheet peptides from Aβ form homochiral pleated β-sheets rather than heterochiral rippled β-sheets

Abstract: In aqueous solution, mixtures of l- and d- macrocyclic β-sheet peptides derived from Aβ self-assemble to form homochiral pleated β-sheets but do not co-assemble to form heterochiral rippled β-sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…Liu and Gellman showed that peptides designed to form two stranded β-hairpins, composed of half L and half D residues, did not exhibit heterochiral stand pairing when studied in solution. Similar observations were made by Nowick and co-workers from solution-state NMR studies conducted on both cyclic β-sheet peptides derived from Aβ17–23 and Aβ30–36 and hydrophobic β-turn peptide mimics, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Liu and Gellman showed that peptides designed to form two stranded β-hairpins, composed of half L and half D residues, did not exhibit heterochiral stand pairing when studied in solution. Similar observations were made by Nowick and co-workers from solution-state NMR studies conducted on both cyclic β-sheet peptides derived from Aβ17–23 and Aβ30–36 and hydrophobic β-turn peptide mimics, respectively.…”
Section: Discussionsupporting
confidence: 85%
“… 32 Wallach's rule was recently invoked to attempt to explain the tendency for racemic peptides to form rippled β-sheets in the solid state. 35 It is important to note, however, that racemic peptide mixtures may produce racemic crystals without forming a rippled β-sheet. For example, the enantiomers in the racemic mixture of the GSTSTA peptide repeat from the ice-nucleation protein InaZ, self-sorted locally into pleated β-sheet layers that mated via mirror-image steric zippers in the racemic crystal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All publication charges for this article have been paid for by the Royal Society of Chemistry rippled b-sheets. 34,35 The development of a rm crystallographic foundation is, therefore, of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as soon as the terminal benzyl substituents are changed into ethyl groups while conserving the rest of the oligourea structure, the nanorings do not form and oligomeric chains emerge instead. Presumably, the assembly in the solid phase is also driven by crystal packing, 32 i.e. involves other noncovalent interactions between the layers or chains (as evidenced by a NCI plot of antiparallel chains of 4b (see Figure SI 53); dipole moment alignment/cancellation, etc.)…”
Section: Aggregation In the Solution Phasementioning
confidence: 99%